Effects of milk cooling: A case study on milk supply chain for a factory in Ethiopia (Presentation) - Dijkink, Bert; Esveld, Erik; Vollebregt, Martijntje; Broeze, Jan (2019)
Evaluation of different chilling scenarios for improving and increasing the milk supply. Summary of study findings.